Genotoxicity evaluation of Chlorfenapyr in exposed freshwater African catfish Clarias gariepinus using micronucleus test - Imeh Kokoete Esenowo; Akwaowo U. Nelson; Chibuisi G. Alimba; Ndifreke D. Ekpo; Okeh C. Emmanuel (Syiah Kuala University, 2021)
Chlorfenapyr is a new formulated insecticide targeted against insecticide resistant species. Its application in targeting harmful aquatic insects may potentially contaminate aquatic environment. This study is to evaluate its genotoxic effects on non-targeted aquatic biota. The study assessed the genotoxic potentials of chlorfenapyr in African catfish (Clarias gariepinus) using the micronucleus (MN) test. Juvenile stage of C. gariepinus were exposed to different concentrations; 5.00 – 15.00 mgL-1 of chlorfenapyr for 96 hours, peripheral blood was collected through the caudal vein and examined for micronucleus induction in the erythrocytes. The tested concentrations of chlorfenapyr did not elicit significant [F (5, 18) = 0.167, p 0.971] increase in MN formation and other nuclear abnormalities in the peripheral erythrocytes of C. gariepinus. The outcome of this study gives credence to the view that chlorfenapyr is not clastogenic and or aneugenic to non-targeted aquatic vertebrate with reference to fish (C. gariepinus).